Species Diversity and Distribution Area of Lichen in Baturraden Botanical Garden, Banyumas - Yulianti, Siska Dwi; Mulyaningrum, Eko Retno; Rahayu, Praptining (Universitas Ahmad Dahlan, 2022)
Lichen is a symbiotic organism between fungi and algae which is used as a bioindicator of air pollution. This study aims to determine the diversity of species and distribution areas of lichen in Baturraden Botanical Garden, Banyumas Regency by using purposive random sampling method. Sampling was carried out at three stations, namely flora of Java forest (Javanese mountain plants), resin tree forest (damar forest), and natural forest. Based on the results of the research at the three observation stations, 10 species of lichen were found. The lichens found belonged to 8 families including Cryptothecia striata (Family Arthoniaceae), Dirinaria picta (Family Caliciaceae), Graphis scripta and Diorygma poitaei (Family Graphidaceae), Parmotrema austrosinense and Parmotrema perlatum (Family Parmeliaceae), Psilolechia lucida (Family Psilolechiaceae), Lepraria caeosioalba (Family Stereocaulaceae), Normandina pulchella (Family Verrucariaceae), Opegrapha atra (Family Opegraphaceae). The thallus types of lichen found were foliose, crustose, and squamulose species. The average value of the species diversity index from the three stations is H' = 1.493 in the moderate abundance category. The distribution of lichens in Baturraden Botanical Garden is influenced by climatic factors (light intensity, air temperature, humidity), topographic factors (altitude) and environmental conditions.